Ubiquitin C-Terminal Hydrolase 1 and Phosphorylated Axonal Neurofilament Heavy Chain in Infants Undergoing Cardiac Surgery: Preliminary Assessment as Potential Biomarkers of Brain Injury. Issue 4 (July 2018) - Lee, Timothy; Chikkabyrappa, Sathish M.; Reformina, Diane; Mastrippolito, Amanda; Chakravarti, Sujata B.; Mosca, Ralph S.; Shaw, Gerry; Malhotra, Sunil P.
Background: There are no reliable markers to assess brain injury in neonates following cardiac surgery. We examine ubiquitin C-terminal hydrolase 1 (UCHL1) and phosphorylated axonal neurofilament heavy chain (pNF-H), neuronal-specific biomarkers released following axonal and cortical injury, in neonates undergoing cardiac surgery involving cardiopulmonary bypass (CPB) and deep hypothermic circulatory arrest (DHCA). Methods: Twenty-six patients younger than three months were prospectively enrolled (CPB only, n = 12 and DHCA, n = 14). Healthy newborns (n = 22) served as the control. Blood samples were collected preoperatively and postoperatively upon intensive care unit admission (hour 0) and subsequently at 12, 24, 36, and 48 hours. Serum was tested for UCHL1 and pNF-H using enzyme-linked immunosorbent assay. Concomitant arterial blood gas, lactate, and cerebral near-infrared spectroscopy (NIRS) monitoring were performed. Results: Ubiquitin C-terminal hydrolase 1 showed a significant rise at 0 hours in the DHCA group compared to baseline (74.9 ± 13.7 pg/mL vs 33.9 ± 37.3 pg/mL, P < .0001). Levels returned to baseline at 12 hours. There was an early rise in UCHL1 at 0 hours in the CPB group, P = .09. Phosphorylated axonal neurofilament heavy chain was decreased at 0 hours in both the CPB and DHCA groups compared to baseline, P = .06. There was no difference between control and baseline levels of UCHL1 ( P = .9) or pNF-H ( P = .77). Decreased NIRS was observed in the DHCA group at 0 hours (57.3 ± 10.5) versus baseline (64.2 ± 12.3), but not significant ( P = .21). There was no correlation between biomarkers and NIRS at 0 hours. Conclusion: A rapid rise in UCHL1 levels was observed in the DHCA group, suggesting that it may be a marker for acute brain injury. Follow-up with neurodevelopmental studies is ongoing.